2020
DOI: 10.3390/s20247084
|View full text |Cite
|
Sign up to set email alerts
|

Antidisturbance Control for AUV Trajectory Tracking Based on Fuzzy Adaptive Extended State Observer

Abstract: In this paper, an output-feedback fuzzy adaptive dynamic surface controller (FADSC) based on fuzzy adaptive extended state observer (FAESO) is proposed for autonomous underwater vehicle (AUV) systems in the presence of external disturbances, parameter uncertainties, measurement noises and actuator faults. The fuzzy logic system is incorporated into both the observers and controllers to improve the adaptability of the entire system. The dynamics of the AUV system is established first, considering the external d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…In addition, the experiments verify that the controller has strong robustness. Wu et al [16], Wang et al [17] and Kang et al [18] make improvements on the basis of the adaptive controller, which is verified in the field of motion control of AUVs. Zhang et al [19] present a sliding mode variable structure control algorithm, and simulation results show that this algorithm has advantages of high control accuracy and strong robustness.…”
Section: Introductionmentioning
confidence: 84%
“…In addition, the experiments verify that the controller has strong robustness. Wu et al [16], Wang et al [17] and Kang et al [18] make improvements on the basis of the adaptive controller, which is verified in the field of motion control of AUVs. Zhang et al [19] present a sliding mode variable structure control algorithm, and simulation results show that this algorithm has advantages of high control accuracy and strong robustness.…”
Section: Introductionmentioning
confidence: 84%
“…An ADRC method based on fuzzy adaptive ESO (extended state observer) was proposed for trajectory tracking of AUV. The simulations indicated that the method outperformed others in terms of tracking accuracy and robustness [10]. A depth ADRC method for AUV was feasible and effective [11].…”
Section: Introductionmentioning
confidence: 91%
“…The motion equations are usually divided into two independent subsystems, the longitudinal one and the lateral one [31]. Omitting the heave, roll, and pitch modes, the motion equations in the horizontal plane are sketched in Equation (10).…”
Section: Motion Equations In the Horizontal Planementioning
confidence: 99%
“…In this paper, a three-layer feed-forward RBF-NN is used to construct the nonlinear prediction model of Equation (12). The transformation from the input layer to the hidden layer in the NN is nonlinear, while the transformation from the hidden layer to the output layer is linear, and its structure is shown in Figure 3.…”
Section: Design Of Rbf-nn Prediction Modelmentioning
confidence: 99%